2019
DOI: 10.14336/ad.2018.0910
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Yes-Associated Protein Induces Cataract in Mice

Abstract: Cataract is a major cause of blindness worldwide, its complicated and unclear etiopathogenesis limit effective therapy. Here, we found that Yap, a downstream effector of the Hippo pathway, is specifically expressed in lens epithelial cells and Yap conditional knockout (cKO) in the lens leads to cataract. Histologically, Yap deficient lens show fewer epithelial cells, retention of nuclei and accumulation of morgagnian globules in the transitional zone and the posterior area. Mechanistically, GFAP-mediated Yap c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Abnormal reactive astrogliosis and microglial activation are observed in YAP knockout mice during cerebral development. Hence, astroglial YAP deletion leads to excessive activation of inflammatory pathways, which potentiates the proinflammatory effects of reactive astrogliosis [ 32 , 63 ]. YAP has also been shown to play an important role in regulating cellular junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal reactive astrogliosis and microglial activation are observed in YAP knockout mice during cerebral development. Hence, astroglial YAP deletion leads to excessive activation of inflammatory pathways, which potentiates the proinflammatory effects of reactive astrogliosis [ 32 , 63 ]. YAP has also been shown to play an important role in regulating cellular junctions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that Yap1 conditional knockout mice developed cataracts with reduced LEC proliferation, however whether or not the LEC apoptosis had also been affected was not clear. 31 From a therapeutic perspective, inhibition of YAP1 activity could potentially be used as an anti-cancer therapy to limit both cancer growth and metastasis. 56 Our finding on the regulation of adult lens homeostasis by YAP1 expression highlights the importance of balancing Yap1 activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Yap activity is essential for maintenance of LEC progenitor activity by preserving self-renewal, and inhibiting apoptosis and precocious differentiation. 31 , 32 In addition, Yap plays a crucial role in maintaining LEC and fiber morphology via stabilizing apical polarity complex and junctional proteins. 32 Inhibition of YAP with Verteporfin suppressed FGF-induced lens cell proliferation and ablated cell elongation during lens fiber differentiation.…”
mentioning
confidence: 99%
“…Recently, the functions of YAP signaling in astrocytes were evaluated. Abnormal reactive astrogliosis and microglial activation are observed in YAP knockout mice during cerebral development.Hence,astroglial YAP deletion leads to excessive activation of in ammatory pathways, which seems to aggravate dysfunction of astrocytes and the proin ammatory effects of reactive astrogliosis [28,63].Interestingly,YAP has been shown to play an important role in regulating cellular junctions. Inhibition of its transcriptional activity at the plasma membrane can disrupt cellular contacts [64].Yang et al found that astrocytic Cx43 reduces the nuclear translocation of YAP in a hemoglobin mouse model [27].…”
Section: Discussionmentioning
confidence: 99%